Failure Mode and Stability of Excavation Face on Shield Tunnel Undercrossing Existing Tunnel - Xue, Fei; Zhang, Mengxi (Civil Engineering Journal, 2019)
The supporting pressure value of excavation face directly determines the stable state of excavation face, and its value will directly lead to instability of excavation face if the value is too small. When the shield is underneath the existing tunnel, special attention should be paid to the support pressure setting of the shield working face. When setting support pressure, the rigidity constraint of existing tunnel on surrounding soil should be fully considered. In this paper, we used ABAQUS software to analyse the failure mode of the soil around the existing tunnel due to the instability of the excavation surface caused by the small pressure setting of the excavation face, which is caused by the small pressure setting of the excavation face. By using the method of theoretical analysis, we optimized the prism in the traditional wedge model to chamfer platform with different opening angles to make it closer to the actual situation, and calculated the critical support pressure of shield tunnel face when it passes through the built tunnel. The research results can provide a reference for the effective value of support force of shield excavation face when the shield tunnel passes under the existing tunnel at a short distance.